2017
DOI: 10.1016/j.freeradbiomed.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of lipid peroxidation products – F4-neuroprostanes, F3-neuroprostanesn-6 DPA, F2-dihomo-isoprostanes and F2-isoprostanes ‐ in the evaluation of the allograft function in renal transplantation

Abstract: F-neuroprostanes, F-neuroprostanes, and F-dihomo-isoprostanes, metabolites of non-enzymatic lipid peroxidation of polyunsaturated fatty acids [docosahexaenoic acid, n-6 docosapentanoic acid, and adrenic acid respectively], have become important biomarkers for oxidative stress in several diseases like epilepsy and alzheimer. These biomarkers and the 15-F-isoprostane (also known as 8-iso-PGF) a F-isoprostane isomer measured as reference oxidative marker at systemic level, were analyzed by UHPLC-QqQ-MS/MS in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The present work describes a reliable and sensitive UPLC-MS/MS method for the simultaneous determination of 17 analytes (F 2 -IsoPs, prostaglandins, F 4 -NeuroPs, F 2 -dihomo-IsoPs, dihomo-IsoFs) and 4 total parameters (IsoP, NeuroP, IsoF, NeuroF) in urine samples. Of note, most of these analytes have not been measured in previous works found in literature [38,42], and the lack of validated liquid chromatographic methods to determine these new set of lipid peroxidation biomarkers in urine human samples adds relevance to this new method. The described UPLC-MS/MS method can be considered a simple alternative to previously published methods, which employ chemical derivatization and gas chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…The present work describes a reliable and sensitive UPLC-MS/MS method for the simultaneous determination of 17 analytes (F 2 -IsoPs, prostaglandins, F 4 -NeuroPs, F 2 -dihomo-IsoPs, dihomo-IsoFs) and 4 total parameters (IsoP, NeuroP, IsoF, NeuroF) in urine samples. Of note, most of these analytes have not been measured in previous works found in literature [38,42], and the lack of validated liquid chromatographic methods to determine these new set of lipid peroxidation biomarkers in urine human samples adds relevance to this new method. The described UPLC-MS/MS method can be considered a simple alternative to previously published methods, which employ chemical derivatization and gas chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprostanoids, the metabolites of non-enzymatic lipid peroxidation of polyunsaturated fatty acid (PUFA), are measured to assess in vivo oxidative stress status [1,2]. Among all the metabolites from PUFAs, 15-F 2t -isoprostane (15-F 2t -IsoP) derived from arachidonic acid (AA) has been largely studied in medical research [3][4][5]. Also, 15-F 2t -IsoP (also referred to as 8-iso-PGF 2α ) has been identified to be the most abundant F 2 -IsoP isomer in the free radical-induced AA oxidation [6] and elevated levels are closely related for example, to inflammation and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it was shown that NeuroPs and not IsoPs are the critical metabolites for neuronal damage. Among all the F 4 -NeuroP molecules, only a handful of the isomers are characterized in neuro-pathological conditions and so far, 4-F 4t -NeuroPs and 10-F 4t NeuroPs are considered to be the most represented [8,[15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, F 3t -NeuroP n-6 a metabolite of DPA and F 2t -dihomo-IsoPs were found useful to assess renal function after kidney transplantation [110,111]. The authors noted that these three metabolites namely, 4-epi-4-F 3t -NeuroP n-6 DPA , ent-7(RS)-7-F 2t -dihomo-IsoP and ent-7(S)-7-F 2t -dihomo-IsoP tended to decrease when kidney function improved and the excretion of urine proteins decreased.…”
Section: Neurops As Oxidative Stress Biomarkersmentioning
confidence: 99%